Pengaruh Penggunaan Teknologi Seluler terhadap Hasil Belajar PAI Peserta Didik SMKITKU Tasikmalaya, Curup Utara, Rejang Lebong - Gunawan Saputra; Johan Efendi; Yunardi Ihsan; Amrullah; Solihin (IIQ An Nur Yogyakarta, 2026)
This study aims to evaluate the impact of mobile technology utilization on Islamic Education (Pendidikan Agama Islam/PAI) learning achievement among students of SMK IT KU Tasikmalaya, North Curup, Rejang Lebong during the 2024/2025 academic year. The background of this study is based on the increasing use of mobile devices among students that have the potential to be used as a medium for digital learning. This study applies a quantitative approach with a correlational study design. The sample consisted of 70 grade X students, of which 60 students were selected using a proportionate stratified random sampling technique. Data were collected through a Likert scale questionnaire, observation, and documentation of academic grades, then analyzed using a simple linear regression method. Descriptive analysis showed that the level of mobile technology use was in the good category (mean = 3.87), followed by PAI learning outcomes which were also in the good category (mean = 3.72). However, the results of the regression test showed a regression coefficient of 0.275 with a significance of 0.092 (> 0.05), which indicated there was no statistically significant effect between mobile technology use and PAI learning outcomes. The coefficient of determination (R²) value of 0.010 indicates that mobile technology only contributes 1.04% to the variation in learning outcomes, while 98.96% is influenced by other variables. This finding indicates that although there is a positive relationship in the use of mobile technology, its utilization has not had a significant effect on improving PAI learning outcomes. Therefore, increased digital literacy, pedagogical supervision, and a more planned technology integration strategy are needed so that the use of mobile technology can function effectively in supporting the PAI learning process.